2020
DOI: 10.1590/2317-1545v42231384
|View full text |Cite
|
Sign up to set email alerts
|

Reserve mobilization in soybean seeds under water restriction after storage

Abstract: Germination does not guarantee plant establishment if there is no efficient and enough reserve mobilization from seeds to the initial seedling growth, mainly in adverse situations. Therefore, this study aimed to evaluate the mobilization of reserves in soybean seeds under water restriction. Four soybean seed lots previously stored for one year were used in the study. To simulate water stress, we used polyethylene glycol (PEG) solutions at concentrations of 0.0, -0.1, and -0.2 MPa. The number of normal, infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Soybean seeds with a high percentage of germination and vigor result in plants that grow and develop quickly, regardless of edaphoclimatic conditions, culminating in a rapid establishment of crops and closing of the lines, which also helps the control of weeds (Krzyzanowski et al, 2018). Seeds with higher physiological quality result in seedlings with a greater dry matter accumulation (Oliveira et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Soybean seeds with a high percentage of germination and vigor result in plants that grow and develop quickly, regardless of edaphoclimatic conditions, culminating in a rapid establishment of crops and closing of the lines, which also helps the control of weeds (Krzyzanowski et al, 2018). Seeds with higher physiological quality result in seedlings with a greater dry matter accumulation (Oliveira et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…As observed in this study, the water restrictions imposed on the plants were responsible for reducing the 1000-seed weight (Table 3). T. F. Oliveira et al (2020) observed that soybean seeds under drought had a higher consumption and lower translocation of reserves to the embryo, reducing the seedling vigor. Therefore, the results found can be related to the efficiency of reserve translocation from the wheat plants to the seeds, without, however, affecting yield.…”
Section: Resultsmentioning
confidence: 99%
“…However, even at reduced temperatures, the metabolism may remain active during storage (Bonjovani & Barbedo, 2019) and is probably more intense in seeds that had not been predried. Wet storage expose the seeds to a stress condition and, according to Oliveira et al (2020), when the amount of water available is not enough to complete germination, it may occur a disordinated consumption of reserves, leading to viability loss.…”
Section: Resultsmentioning
confidence: 99%